Every Young Athlete Counts: Are Tailored Doping Prevention Programs Necessary in Young Elite Sports? - Pöppel, Katharina; Büsch, Dirk (Frontiers in Sports and Active Living, 2022)
Conclusions from doping prevention literature recommend tailored anti-doping education for athletes’ specific needs. Newer approaches like the International Standard for Education of the World Anti-Doping Agency (2021b) recommend a needs assessment before implementing measures. The International Standard for Education refers to the type of sports and its associated risk for doping. Following this idea, elite athletes from different types of sports should differ in their prerequisites for doping prevention. Consequently, the guiding research question focused on exploring the doping-prevention-related background of young athletes as a particular group for prevention efforts. Sixty young elite athletes (58.3 % male) took part in a cross-sectional online survey, which was quantitatively analyzed. Participants included 26 athletes from a sport with low doping prevalence (sailing) and 34 athletes from a sport associated with high doping prevalence (wrestling). Sailors and wrestlers differed concerning the perceived resistance against doping temptations (p=.031, r=.31) and the estimated actual doping prevalence regarding sports in general (national frame: p<.001, r=.60; international frame: p=.013, r=.43). No differences between the two types of sports occurred, referring to doping attitudes, tendency to disengage morally, or topics athletes wish to learn about during doping prevention measures. All results indicated a good baseline for doping prevention with young elite athletes at the beginning of their careers. There is no sport-specific needs profile that could be used as a base for tailored measures. However, the data suggest that a differentiated consideration of gender could be helpful in the planning of doping prevention measures.